Komparasi keadilan dalam penyelesaian kasus aul saat pembagian waris antara konsep ibn abbas dan imam syafi’i - Nashir, Izuddin Sulthan (Maliki Interdisciplinary Journal, 2026)
This study examines the comparative concept of justice in resolving cases of ‘aul between the views of Ibn ‘Abbās and Imam al-Shāfi‘ī. The issue of ‘aul arises when the total fixed shares of heirs exceed the available estate, requiring a corrective mechanism. Ibn ‘Abbās maintains a literal adherence to Qur’anic texts and therefore rejects the concept of ‘aul, considering it unsupported by explicit textual evidence. Imam al-Shāfi‘ī, on the other hand, accepts ‘aul as a form of ijtihād rooted in qiyās, maslahah, and distributive justice. Using a qualitative literature-based approach, this study analyzes the usul foundations, interpretive methods, and justice considerations employed by both scholars. The findings indicate that while Ibn ‘Abbās provides strong textual authority, his approach is less applicable in practical distribution scenarios where the estate is insufficient. Imam al-Shāfi‘ī offers a more comprehensive and adaptable framework, allowing proportional adjustments to maintain fairness. Thus, the concept of ‘aul in the Shāfi‘ī tradition is more contextually relevant for modern inheritance practices that seek to uphold substantive justice.